Peran Malaikat Berdasarkan Kisah Para Rasul 12:5-12 - Elkana, Samuel (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2021)
All human beings must have experienced times of darkness and gloom, wilderness, sadness, fear or disappointment. Especially in our day that is filled with worldwide suffering. Likewise these days, the phenomenon of the spirit world is increasingly widespread and has become the attention of quite a number of Christians in this end of time. Like some people with horoscopes, palm readers, and all kinds of new age teaching. Christian faith must remain firm to believe that to this day angels are still actively sent by God to help believers. The author uses qualitative research methods in the form of exegesis and literature studies to explain that the example of the role of angels according to Acts 12:5-12 is very important for the life of a believer.